Free pedagogic robotics: socio-digital inclusion and democratization of knowledge - Mill, Daniel (2010)
This paper proposes the development of a dynamic educational environment based on the use of robotics as educational technology. This text explores the relationship between free software, discarded computer equipment and education, seeking to articulate proposals for free software with the processof construction of knowledge and with principles of social inclusion. The development of pedagogical activities using discarded equipment and the opening of source code for computer programs constitutes a rich possibility for the “democratization” of accessto cultural and technological goods, as well as of knowledge.